2020
DOI: 10.3390/math8071046
|View full text |Cite
|
Sign up to set email alerts
|

Self-Similar Models: Relationship between the Diffusion Entropy Analysis, Detrended Fluctuation Analysis and Lévy Models

Abstract: Financial and geophysical data, like many other low and high frequency time series, are known to exhibit some memory effects. These memory effects may be long or short, permanent or temporal depending on the event that is being modeled. The purpose of this study is to investigate the memory effects characterized by the financial market closing values and volcanic eruption time series as well as to investigate the relation between the self-similar models used and the Lévy process. This paper uses highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…For the monofractal and multifractal noise-like time series, we observe that H c α is approximately equal to 1 while Hα exceeds 1. This deviates from the inverse relationship between the Hurst exponents and the scaling exponents of the TLF for Gaussian noise as discussed in the paper [4]. This highlights the overestimation of the Hurst exponent of the DFA approach that happens in practice.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…For the monofractal and multifractal noise-like time series, we observe that H c α is approximately equal to 1 while Hα exceeds 1. This deviates from the inverse relationship between the Hurst exponents and the scaling exponents of the TLF for Gaussian noise as discussed in the paper [4]. This highlights the overestimation of the Hurst exponent of the DFA approach that happens in practice.…”
Section: Discussionmentioning
confidence: 63%
“…The results are shown in Table 4 where the Hurst exponent of the CDFA is compared with that of the DFA and the scaling exponents (α) of the TLF. In [4], a relationship was established between the Hurst exponent of the DFA and the α exponent of the TLF. The CDFA is also shown to satisfy this relation, thus making it possible to extract the α exponent of the TLF from the Hurst exponent of the CDFA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detrended fluctuation analysis. Peng et al [38] proposed the Detrended Fluctuation Analysis (DFA) while examining a sequence of DNA nucleotides to study the self-similarity [35] and long-range dependence of time series. From the moment it was submitted to date, DFA has become a widely used method for determining fractal scaling properties and detecting long-range correlations in non-stationary time series.…”
Section: Data Characterizationmentioning
confidence: 99%
“…A number of studies conducted in recent years have shown that many systems in nature generate time series with fractal behaviour [1][2][3][4][5][6]. Examples of such time series are: series of intervals between consecutive heartbeats [2,3,7], economic data on exchange rates [4], electricity prices [5], geophysical data on temperature, precipitation, tides [6,[8][9][10], etc. For the analysis of this type of processes, methods are applied that allow the determination of the global characteristics of the processes as well as the peculiarities of their local structures.…”
Section: Introductionmentioning
confidence: 99%